2005
DOI: 10.3102/01623737027002111
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teaching in the United States Today (and Tomorrow): Results From the TIMSS 1999 Video Study

Abstract: The Third International Mathematics and Science Study (TIMSS) 1999 Video Study examined eighthgrade mathematics teaching in the United States and six higher-achieving countries. A range of teaching systems were found across higher-achieving countries that balanced attention to challenging content, procedural skill, and conceptual understanding in different ways. The United States displayed a unique system of teaching, not because of any particular feature but because of a constellation of features that reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(112 citation statements)
references
References 24 publications
4
107
1
Order By: Relevance
“…One defining characteristic of mathematics instruction is that it is choreographed through the teacher's selection and implementation of tasks and activities. Tasks and subsequent task activities create learning opportunities and determine the internal logic of instruction, the level of challenge, and the level of understanding that can be attained (De Corte, Greer, & Verschaffel, 1996;Hiebert et al, 2005). Knowledge of the potential of mathematical tasks to facilitate learning is thus a key dimension of PCK.…”
Section: Conceptualizing and Assessing Ck And Pck Separatelymentioning
confidence: 99%
“…One defining characteristic of mathematics instruction is that it is choreographed through the teacher's selection and implementation of tasks and activities. Tasks and subsequent task activities create learning opportunities and determine the internal logic of instruction, the level of challenge, and the level of understanding that can be attained (De Corte, Greer, & Verschaffel, 1996;Hiebert et al, 2005). Knowledge of the potential of mathematical tasks to facilitate learning is thus a key dimension of PCK.…”
Section: Conceptualizing and Assessing Ck And Pck Separatelymentioning
confidence: 99%
“…But they do paint a picture of instruction after the NCTM report, and thus we can use them to evaluate whether the vision of the standards was realized in American classrooms. See Hiebert et al (2005); Banilower et al (2013). 24 https://en.wikipedia.org/wiki/Niche_construction.…”
Section: The Common Corementioning
confidence: 99%
“…In the United States, the focus on certification has been informed by research on out-of-field teaching (Ingersoll, 1999(Ingersoll, , 2001 3 and by comparative and international studies that identified the weaknesses in instructional practices and environments surrounding U.S. teachers in comparison with those of teachers in high-achieving countries (Ginsburg, Cooke, Leinwand, Noell, & Pollock, 2005;Hiebert et al, 2005;LeTendre, Baker, Akiba, Goesling, & Wiseman, 2001;Stigler & Hiebert, 1999;Stigler & Stevenson, 1991).…”
Section: Teacher Quality Around the Worldmentioning
confidence: 99%